Why Do People Buy Dupe Cosmetics? - Nursafira, Ratna Alya; Nathania, Vanessa; Handoko, Rudy; Budiman, Arief (Kajian Branding Indonesia, 2024)
The society often buy counterfeits to fulfill their functional needs with lower-priced products. In regard to this, researchers aim to dig deeper insights about the current trend in the cosmetics industry: dupes, which are knockoff products that resulted from duplicating an authentic product, but with an entirely different brand identity. The researchers seek to investigate the products of Reveline Stain Plump Tint, Somethinc Ombrella Lip Totem Tint, and Emina Glossy Stain as the dupes of Dior Lip Tint, and consumers’ values while purchasing them. The research design used is case study using the method of Focus Group Discussion. This research aims to complete the existing research gaps from the previous studies regarding counterfeits and dig deeper insight specifically about this dupe phenomenon. The result of this research will then be analyzed and interpreted using the coding method with thematic analysis.